FLOWERING REPRESSOR AAA+ ATPase 1 is a novel regulator of perennial flowering in Arabis alpina. Issue 2 (8th August 2022) - Viñegra de la Torre, Natanael; Vayssières, Alice; Obeng‐Hinneh, Evelyn; Neumann, Ulla; Zhou, Yanhao; Lázaro, Ana; Roggen, Adrian; Sun, Hequan; Stolze, Sara C.; Nakagami, Hirofumi; Schneeberger, Korbinian; Timmers, Ton; et al.
Summary: Arabis alpina is a polycarpic perennial, in which PERPETUAL FLOWERING1 (PEP1) regulates flowering and perennial traits in a vernalization‐dependent manner. Mutagenesis screens of the pep1 mutant established the role of other flowering time regulators in PEP1‐parallel pathways. Here we characterized three allelic enhancers of pep1 ( eop002, 085 and 091 ) which flower early. We mapped the causal mutations and complemented mutants with the identified gene. Using quantitative reverse transcriptase PCR and reporter lines, we determined the protein spatiotemporal expression patterns and localization within the cell. We also characterized its role in Arabidopsis thaliana using CRISPR and in A. alpina by introgressing mutant alleles into a wild‐type background. These mutants carried lesions in an AAA + ATPase of unknown function, FLOWERING REPRESSOR AAA + ATPase 1 ( AaFRAT1 ). AaFRAT1 was detected in the vasculature of young leaf primordia and the rib zone of flowering shoot apical meristems. At the subcellular level, AaFRAT1 was localized at the interphase between the endoplasmic reticulum and peroxisomes. Introgression lines carrying Aafrat1 alleles required less vernalization to flower and reduced number of vegetative axillary branches. By contrast, A. thaliana CRISPR lines showed weak flowering phenotypes. AaFRAT1 contributes to flowering time regulation and the perennial growth habit of A. alpina.